Kenya and the ICC: the politics of the 2007 post-election violence - Fromet De Rosnay, Amandine (Department of Political Studies, 2015)
In December 2007, Kenya held a presidential election. The incumbent was Mwai Kibaki of the Party of National Unity (PNU). His political opponent was Raila Odinga of the Orange Democratic Movement (ODM). The vote was peaceful and described by many in positive terms; that is, a continuation of the positive democratic transition that Kenya began toward the end of the 1990s. However, many in Kenya accused the government of foul play, when the Electoral Commission of Kenya (ECK) delayed declaring a winner for two days. The ECK eventually declared Kibaki President, and rushed the swearing - in ceremony, skipping the stipulated 72 hours. Two days after declaring Kibaki president, Samuel Kivuitu, the chair of the ECK, admitted he did not know whether Kibaki had won the elections. He insisted that he had agreed to release the results and announce Kibaki as president, under pressure from above. Kenya then experienced its worst bout of violence since the Mau Mau rebellion, before independence. The Post - Election Violence (PEV) lasted two months. It was resolved following an agreement, the Kenya National and Reconciliation Dialogue (K N D R), negotiated by a Panel of Eminent Personalities. The fighting parties agreed to form a Government of National Unity (GNU), a Commission of Enquiry into the Post - Election Violence (CIPEV) and an Independent Review Commission on the General elections (Kriegler Commission). The GNU was to have Kibaki reinstated as President, to add the post of Prime Minister for Odinga, and was to undertake a reconciliation and accountability process, prosecuting perpetrators. This thesis seeks to determine what were the politics that led Kenya to prosecute those who bore greatest responsibility for the PEV. More specifically, what were the politics that resulted in selecting the ICC, as the court where individuals were going to be held accountable?